(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cervical screening is the process of detecting and removing abnormal tissue or cells in the cervix before cervical cancer develops. By aiming to detect and treat cervicalneoplasia early on, cervical screening aims at secondary prevention of cervical cancer.The incidence of cervical cancer in areas where more than 20% of U.S. residents live under the poverty line is 18% to 39% higher than areas where less than 10% of residents live below the poverty line